Perceptions and attitudes towards medication error reporting in primary care clinics: A qualitative study in Malaysia - Samsiah, A.; Othman, Noordin; Jamshed, Shazia Qasim; Hassali, Mohamed Azmi (PLOS, 2016)
OBJECTIVE: To explore and understand participants' perceptions and attitudes towards the reporting of medication errors (MEs). METHODS: A qualitative study using in-depth interviews of 31 healthcare practitioners from nine publicly funded, primary care clinics in three states in peninsular Malaysia was conducted for this study. The participants included family medicine specialists, doctors, pharmacists, pharmacist assistants, nurses and assistant medical officers. The interviews were audiotaped and transcribed verbatim. Analysis of the data was guided by the framework approach. RESULTS: Six themes and 28 codes were identified. Despite the availability of a reporting system, most of the participants agreed that MEs were underreported. The nature of the error plays an important role in determining the reporting. The reporting system, organisational factors, provider factors, reporter's burden and benefit of reporting also were identified. CONCLUSIONS: Healthcare practitioners in primary care clinics understood the importance of reporting MEs to improve patient safety. Their perceptions and attitudes towards reporting of MEs were influenced by many factors which affect the decision-making process of whether or not to report. Although the process is complex, it primarily is determined by the severity of the outcome of the errors. The participants voluntarily report the errors if they are familiar with the reporting system, what error to report, when to report and what form to use.